Analisis Pengaruh Implementasi Filsafat Pendidikan Karakter terhadap Peningkatan Perilaku Sosial Siswa di SD Negeri Ciaripin - Neuneu Nurlaela Hasanah; Nisa Pujiani; Mahwa Dalimi; Kun Nurachadijat (Lembaga Yasin AlSys, 2026)
Although character education has been widely examined in various previous studies, studies that specifically discuss the influence of implementing the philosophy of character education on the social behavior of elementary school students remain limited. This study aims to analyze the effect of applying the philosophy of character education on students’ social behavior at SD Negeri Ciaripin. This study used a quantitative approach with an associative survey design, involving 41 Grade VI students selected using saturated sampling. Data were collected using questionnaires and participatory observation, then analyzed using simple linear regression. The results showed that the implementation of the philosophy of character education had a positive and significant effect on students’ social behavior. Students who consistently received reinforcement of character values showed increased empathy, social responsibility, cooperation, and inclusive behavior in the school environment. These findings contribute to the development of character education theory, particularly Thomas Lickona’s concept of moral virtue, and expand understanding of the importance of integrating philosophical values into daily learning. The conclusion of this study affirms that the implementation of the philosophy of character education plays an important role in shaping students’ positive and responsible social behavior. The implications of this study provide theoretical contributions to the development of the character education literature and practical contributions for schools in designing sustainable character value-based learning programs.